Role of Crop Rotation Practices on Soil Health - Mwangi, John (American Journal of Agriculture, 2024)
Purpose: The aim of the study was to examine the role of crop rotation practices on soil health in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Crop rotation enhances soil health by diversifying crops, improving nutrient balance, suppressing diseases, enhancing soil structure, and aiding in weed control. This practice promotes biodiversity, supports nutrient cycling, and contributes to sustainable agriculture while offering economic advantages through increased yields and reduced input costs. Overall, crop rotation plays a vital role in maintaining and improving the long-term health of agricultural soils. Implications to Theory, Practice and Policy: Liebig's law of the minimum, Jensen's theory of crop rotation benefits and Gliessman's agroecological principles may be use to anchor future studies on examining the role of crop rotation practices on soil health in Kenya. Develop extension programs and educational materials to disseminate knowledge about the benefits of crop rotation and provide practical guidance on implementing diverse rotation systems. Governments and agricultural agencies can establish incentive programs, such as subsidies or tax incentives, to encourage farmers to adopt crop rotation practices.